Effect of thermal conductivity and viscosity on cooling performance of liquid quench media. (March 2014) - Ramesh, G.; Narayan Prabhu, K.
<x content-type="archive" xml:space="preserve">Abstract</x> In this present work, the effect of the thermophysical properties of quenchants on its cooling performance was investigated. Water, brine solutions, polymer solutions and mineral oils were chosen to have quench media with varying thermophysical properties. Cooling curve analyses were carried out by using standard ISO/DIS 9950 quench probe. Grossmann H quench severity of the quench media was determined from the relation of H and cooling rate. Cooling curve analysis results showed that the change in thermophysical properties of the quench media had significant effect on the cooling history of the quench probe. The viscosity of the quenchant used for immersion quenching is the most important factor that controls the cooling performance of the quenchant compared to thermal conductivity of the quench medium.